Development of copy number assays for detection and surveillance of piperaquine resistance associated plasmepsin 2/3 copy number variation in Plasmodium falciparum - Ansbro, Megan R. (Malar J, 2020)
BACKGROUND: Long regarded as an epicenter of drug-resistant malaria, Southeast Asia continues to provide new challenges to the control of Plasmodium falciparum malaria. Recently, resistance to the artemisinin combination therapy partner drug piperaquine has been observed in multiple locations across Southeast Asia. Genetic studies have identified single nucleotide polymorphisms as well as copy number variations in the plasmepsin 2 and plasmepsin 3 genes, which encode haemoglobin-degrading proteases that associate with clinical and in vitro piperaquine resistance. RESULTS: To accurately and quickly determine the presence of copy number variations in the plasmepsin 2/3 genes in field isolates, this study developed a quantitative PCR assay using TaqMan probes. Copy number estimates were validated using a separate SYBR green-based quantitative PCR assay as well as a novel PCR-based breakpoint assay to detect the hybrid gene product. Field samples from 2012 to 2015 across three sites in Cambodia were tested using DNA extracted from dried blood spots and whole blood to monitor the extent of plasmepsin 2/3 gene amplifications, as well as amplifications in the multidrug resistance transporter 1 gene (pfmdr1), a marker of mefloquine resistance. This study found high concordance across all methods of copy number detection. For samples derived from dried blood spots, a success rate greater than 80% was found in each assay, with more recent samples performing better. Evidence of extensive plasmepsin 2/3 copy number amplifications was observed in Pursat (94%, 2015) (Western Cambodia) and Preah Vihear (87%, 2014) (Northern Cambodia), and lower levels in Ratanakiri (16%, 2014) (Eastern Cambodia). A shift was observed from two copies of plasmepsin 2 in Pursat in 2013 to three copies in 2014–2015 (25% to 64%). Pfmdr1 amplifications were absent in all samples from Preah Vihear and Ratanakiri in 2014 and absent in Pursat in 2015. CONCLUSIONS: The multiplex TaqMan assay is a robust tool for monitoring both plasmepsin 2/3 and pfmdr1 copy number variations in field isolates, and the SYBR-green and breakpoint assays are useful for monitoring plasmepsin 2/3 amplifications. This study shows increasing levels of plasmepsin 2 copy numbers across Cambodia from 2012 to 2015 and a complete reversion of multicopy pfmdr1 parasites to single copy parasites in all study locations.